Islam Indonesia dan Demokratisasi: Dari Transisi ke Konsolidasi - Testriono, Testriono (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
Mirjam Kunkler and Alfred Stepan (eds). 2013. Democracy and Islam in Indonesia. New York: Columbia University Press. xv + 252pp.Donald L. Horowitz. 2013. Constitutional Change and Democracy in Indonesia. Cambridge: Cambridge University Press. xviii + 326pp.The two reviewed books provide explanations for the success of Indonesia’s democratization. Kunkler and Stepan’s (2013) edited volume, Democracy and Islam in Indonesia, emphasizes the political actors (agency) in explaining democratization in Indonesia. Meanwhile, Horowitz’s (2013) Constitutional Change and Democracy in Indonesia focuses on institutions and the strategies of institutional reform chosen by political actors during democratization. Both works provide careful evaluation on the relatively stable development of Indonesian democracy. Examining the social, political, and institutional foundations that facilitate the consolidation of Indonesia’s democracy, the two works analyze why and how the democratic transition in Indonesia proceeded to a consolidation stage. Different form Kunkler and Stepan’s edited volume, which evaluates the state of Indonesian democracy by refererring to the criteria offered by democratic consolidation framework, Horowitz’s work moves farther revealing why the democratic processes have occurred in the sequence and manner that they did.DOI: 10.15408/sdi.v22i3.2411